Analisis Common Size dan Analisis Trend dalam Kinerja Keuangan PT Ace Hardware Indonesia TBK Tahun 2021-2022 - Hidayat, Rindiani Sofah; Sulistiyo, Hari (Peneliti.net, 2024)
This research discusses the use of Common Size Analysis and Trend Analysis as strategic tools for Company Financial Performance. Common size analysis provides detailed insight into cost structures, allowing companies to determine areas to improve operations. This research aims to assess the performance of PT ACE Hardware Indonesia Tbk's financial reports for 2021-2022. The method used by researchers is descriptive comparative by carrying out vertical comparisons from the previous year. In the financial report of PT Ace Hardware Indonesia, Tbk 2021-2022, the results of common size and trend calculations show that gross profit and net profit have decreased as a percentage of sales. Trend analysis shows an increase in operational costs and cost of goods sold which need to be evaluated to increase operational efficiency.